СURRENT STATE OF THE OIL AND GAS INDUSTRY AS A SOURCE OF DEMAND OF INNOVATIONS - A. Volkov; R. Shepelev (Вестник университета, 2019)
Current state of innovative development in the oil and gas industry has been considered. The importance of the oil and gas industry for the economic development of the Russian Federation has been noted. Comparison of the results of research and development funding levels among domestic and foreign companies has been performed. A system of private indicators to assess the level of development of innovative activity of companies, taking into account the financial, production and technological indicators of companies, has been proposed. The results of testing this system of indicators have been adduced. The main approaches to the formation of Innovative Development Programs of companies with state participation have been considered. The main tasks of technological development for the domestic oil and gas complex have been highlighted.